Average Values and Racial Differences of Neutrophil Lymphocyte Ratio among a Nationally Representative Sample of United States Subjects - Azab, Basem; Camacho-Rivera, Marlene; Taioli, Emanuela (PloS one, 2014)
Several studies reported the negative impact of elevated neutrophil/lymphocyte ratio (NLR) on outcomes in many surgical and medical conditions. Previous studies used arbitrary NLR cut-off points according to the average of the populations under study. There is no data on the average NLR in the general population. The aim of this study is to explore the average values of NLR and according to race in adult non-institutional United States individuals by using national data. The National Health and Nutrition Examination Survey (NHANES) of aggregated cross-sectional data collected from 2007 to 2010 was analyzed; data extracted included markers of systemic inflammation (neutrophil count, lymphocyte count, and NLR), demographic variables and other comorbidities. Subjects who were prescribed steroids, chemotherapy, immunomodulators and antibiotics were excluded. Adjusted linear regression models were used to examine the association between demographic and clinical characteristics and neutrophil counts, lymphocyte counts, and NLR. Overall 9427 subjects are included in this study. The average value of neutrophils is 4.3 k cells/mL, of lymphocytes 2.1k cells/mL; the average NLR is 2.15. Non-Hispanic Black and Hispanic participants have significantly lower mean NLR values (1.76, 95% CI 1.71-1.81 and 2.08, 95% CI 2.04-2.12 respectively) when compared to non-Hispanic Whites (2.24, 95% CI 2.19-2.28-p<0.0001). Subjects who reported diabetes, cardiovascular disease, and smoking had significantly higher NLR than subjects who did not. Racial differences regarding the association of smoking and BMI with NLR were observed. This study is providing preliminary data on racial disparities in a marker of inflammation, NLR, that has been associated with several chronic diseases outcome, suggesting that different cut-off points should be set according to race. It also suggests that racial differences exist in the inflammatory response to environmental and behavioral risk factors.